Development of Visual Arts Activities to Strengthen the Dimensional Capabilities Grade Students at One in the Office of Elementary Phetchabun region 1 - Anuntaard, Alissana; Ngamrugrot, Aphichart (RMUTK Journal of Liberal Arts, 2024)
The objectives of this research were to 1) develop a set of visual arts activities to enhance the dimensional abilities of Grade 1 students, 2) To compare the dimensional abilities before and after using visual arts activities to enhance the dimensional relationships of grade 1 students. The subjects used in this research were Grade 1 students of Dong Khui Wittayakarn School under Phetchabun Primary Education Area Office District 1; a total of 30 students were selected by a simple random sampling of 1 classroom. The researchers conducted the experiments which took two hours per week for 5 consecutive weeks. The tools used in the research were a set of visual arts activities to enhance the dimensional abilities of Grade 1 students; namely, (1) a set of visual arts and drawing activities, (2) a set of visual arts and printmaking, (3) visual art and sculpting, (4) visual art and invention, (5) visual art and painting, and an activity to improve students’ dimensional skills of Grade 1 students. The results showed that 1) the efficiency development of the visual arts activity set was 81.70/83.60, which was higher than the established threshold of 80/80. 2) Regarding the dimensional abilities, the post-class score in which the students used the visual arts activity sets was statistically significantly higher than the pre-class score before the students used the visual arts activity sets, at the 0.05 level.